A compact hydrogen sensor based on the fiber-optic Fabry-Perot interferometer. (April 2020) - Zhou, Xinlei; Ma, Fengxiang; Ling, Haitao; Yu, Binjun; Peng, Wei; Yu, Qingxu
Highlights: A compact fiber-optic hydrogen sensor based on the F-P interferometer is present. A response time of 185 s and a sensitivity of 1.4 nm/% are obtained. A resolution of 500 ppm and a good repeatability have been demonstrated. The sensor is compact, easy in fabrication, low cost. Abstract: We report an optical fiber hydrogen sensor based on the Fabry-Perot interferometer formed by inserting two ceramic ferrules, one with a flat fiber end facet and the other with a commercial Pd film on their tip, into a matched ceramic sleeve. The response time and sensitivity of the proposed hydrogen sensor are investigated both theoretically and experimentally. A response time of 185 s and a sensitivity of 1.44 nm/% have been obtained. In addition, the resolution and repeatability are investigated experimentally. A resolution of 500 ppm and a good repeatability have been demonstrated. The proposed sensor is compact, easy in fabrication, low cost and has a high potential for hydrogen detection.